Hutchinson, Mildred (audio interview #2 of 3) - Hutchinson, Mildred (b. 10/17/1894 - d. 1/14/2000); Wayman, Phyllis, interviewer
INTERVIEW DESCRIPTION - Hutchinson speaks rather softly in this second interview, making it hard to hear her at times. This is particularly problematic on the second side of the recording (2b), where there is background noise.